Bamboo-based hard carbon material for sodium ion battery as well as preparation method and application of bamboo-based hard carbon material

By using bamboo fibres to prepare bamboo-based hard carbon materials, the performance attenuation problems of sodium ion battery negative electrode materials in the sodium storage process are solved, and high reversible capacity, excellent rate performance and cost-reducing effects are achieved.

CN120191913APending Publication Date: 2025-06-24ZHEJIANG POWER (NINGBO BEILUN) SMART ENERGY CO LTD

Patent Information

Application Number
CN202410303840.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have problems such as volume expansion and dissolution and regeneration of SEI films during sodium storage, resulting in attenuation of the electrode material performance, and the rate performance of porous carbon materials under high current density is not ideal.

Method used

Bamboo fibrils are used as raw materials to prepare bamboo-based hard carbon materials through pretreatment and pyrolysis treatment, controlling the specific surface area, carbon layer spacing, pore structure and closed pore content of the material, and using ammonium chloride and fluoropolymer as pore-forming agents and plasticizers.

Benefits of technology

The reversible capacity, first-circle coulomb efficiency and rate performance of bamboo-based hard carbon materials are improved, the preparation cost is reduced, and the sodium storage capacity of the material and the first-week coulomb efficiency are balanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120191913A_ABST
    Figure CN120191913A_ABST
Patent Text Reader

Abstract

The invention provides a bamboo-based hard carbon material for a sodium ion battery and a preparation method of the bamboo-based hard carbon material. The bamboo-based hard carbon material is prepared from raw materials as follows: bamboo fibers, a pore forming agent and a fluorine-containing polymer, wherein the mass ratio of the natural bamboo fibers to the pore-forming agent is (0.8-1.2): 1. The bamboo-based hard carbon material is prepared by using the raw bamboo fibers as raw materials, pretreating the raw bamboo fibers and then performing pyrolysis treatment; the prepared bamboo-based hard carbon material is characterized in that the carbon layer spacing d002 is 0.376 to 0.399 nm. According to the preparation method disclosed by the invention, the bamboo-based hard carbon material prepared by selecting specific natural bamboo fibers and controlling preparation conditions such as temperature, time, heating rate and atmosphere in pyrolysis treatment has proper specific surface area, carbon layer spacing, pore structure and closed pore content. The bamboo-based hard carbon material disclosed by the invention is applied to a sodium ion battery and has excellent electrochemical properties such as reversible capacity, first-circle coulombic efficiency and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anode materials for sodium-ion batteries, and particularly relates to a bamboo-based hard carbon material for sodium-ion batteries, a preparation method thereof, and an application thereof. Background Art

[0002] As people pay more and more attention to the development of clean energy and high-efficiency energy storage devices, sodium-ion batteries have advantages due to their rich resources, low price, wide distribution, etc. Developing anode materials with high specific capacity, cycling performance, and rate performance is of great significance for the application of sodium-ion batteries. Sodium ions have similar chemical properties to lithium ions, but the sodium resource reserve is 1000 times that of lithium resources. The research on sodium-ion batteries can not only effectively reduce the cost of the battery, but also has important significance for the energy storage field.

[0003] The important properties such as the energy density, rate performance, and cycle life of sodium-ion batteries are closely related to the anode materials. Anode materials for sodium-ion batteries can be roughly divided into three categories according to the sodium storage mechanism: the first category is metals and alloys, such as tin, bismuth, antimony, etc.; the second category is conversion materials, such as various transition metal oxides, sulfides, phosphides, etc.; the third category is adsorption and insertion materials, such as various forms of carbon materials, etc. Metal materials have relatively high reversible specific capacity and low voltage platforms. Metal elements react with sodium during charge and discharge to form binary metal compounds of sodium-metal. Most of the research on them focuses on the elements of the fourth and fifth main groups and the compounds formed by them; among alloy materials, silicon anodes have been widely studied due to their high theoretical capacity and rich resources, but they have problems with poor sodium storage performance. Although metal and alloy anode materials have relatively high reversible specific capacity, the volume expansion and dissolution and regeneration of the SEI film during sodium storage cannot be ignored, resulting in the performance degradation of the electrode materials. Conversion materials are mainly divided into two categories, one is oxides, sulfides, phosphides, etc. formed by transition metals; the other is oxides, sulfides, selenides, phosphides, etc. of active metals. Conversion materials, like metal alloy materials, have the advantage of high specific capacity, and at the same time have more excellent cycling performance than alloy materials. However, when conversion materials are applied in sodium-ion batteries, problems such as electrode pulverization and swelling are likely to occur, and usually the rate performance is poor.

[0004] Due to advantages such as low price, good thermal stability, and low reaction platform voltage, carbon materials have been widely studied as anode materials for sodium-ion batteries. Currently, the widely studied carbon-based anode materials for sodium-ion batteries are mainly divided into the following several types: graphite materials, hard carbon materials, heteroatom-doped carbon materials, etc. Among them, graphite materials are rich in resources, inexpensive and easy to obtain, and have excellent processing performance, and have been successfully applied in the field of lithium-ion batteries. However, due to Na +Graphite has a high diffusion energy barrier and thermodynamic instability, resulting in poor sodium storage effects in graphite-based materials. Hard carbon materials refer to carbon materials that are difficult to graphitize even at a high temperature of 2500°C. They are mainly composed of a microporous structure of an amorphous phase and a short-range ordered graphite-like phase. Due to the presence of more nanopores and large carbon layer spacing, they can better accommodate sodium ions for electrochemical energy storage. However, the sodium storage capacity of both graphite materials and hard carbon materials needs to be improved. The use of heteroatom doping can increase the defects and sodium storage active sites inside the carbon material, and can also improve its conductivity and wettability.

[0005] In the preparation of hard carbon materials, choosing a suitable precursor is a prerequisite for obtaining a high-performance hard carbon negative electrode. The properties of the precursor determine the difficulty of its graphitization, affecting the yield of the carbonization process and the electrochemical properties of the resulting carbon material. Common precursors of hard carbon include high molecular polymers such as resins, cellulose, starch, and sucrose, as well as various biomass raw materials such as nut shells and plants. Biomass materials are low-cost, green and environmentally friendly, and easy to process. Most biomass materials have their own special morphology. The materials are strong and not easy to be destroyed. After conversion, they can still maintain their original morphology well. They are an ideal precursor material. Due to the huge output of bamboo in my country, bamboo-based materials have become one of the best raw materials for my country's native biomass hard carbon materials. Bamboo-based hard carbon negative electrode material is a new type of negative electrode material with the advantages of high capacity, high rate, and long cycle life. Chinese patent CN114890404A discloses a method for preparing bamboo charcoal that can be mass-produced. Different types of bamboo are used as raw materials. After washing, drying, and crushing, they are sintered under the protection of an inert atmosphere to obtain bamboo charcoal black powder. Chinese patent CN117105199A discloses a method for preparing a bamboo-based hard carbon material, which comprises liquid-phase modification and gas-solid modification of peeled bamboo tubes, and then pre-carbonizing, crushing and grading the modified bamboo tubes to obtain a precursor, and then carbonizing to obtain a bamboo-based hard carbon material. However, the preparation process of the material is relatively complicated and the cost is high. However, the preparation process of the above materials still has problems such as complicated process flow and high cost, and the electrochemical performance of the material still needs to be improved.

[0006] Since most hard carbon materials have a small specific surface area and a relatively uniform pore size distribution, their rate performance at high current density is not ideal. However, low-cost carbon materials are the best choice for the commercialization of sodium-ion batteries. Therefore, how to improve the stability of porous carbon materials and enhance their first-cycle coulombic efficiency and rate performance has become the current research focus. Summary of the invention

[0007] In view of the above problems, the present invention provides a bamboo-based hard carbon material for sodium-ion batteries and a preparation method thereof. The present invention uses bamboo fiber as a raw material, which is pretreated and then pyrolyzed to obtain a bamboo-based hard carbon material. In the preparation method of the present invention, by selecting a specific bamboo fiber and controlling the preparation conditions such as temperature, time, heating rate and atmosphere in the pyrolysis treatment, the obtained bamboo-based hard carbon material has a suitable specific surface area, carbon layer spacing, pore structure and closed pore content. When the bamboo-based hard carbon material of the present invention is applied to a sodium-ion battery, it has excellent electrochemical properties such as reversible capacity, first-cycle Coulomb efficiency and rate performance.

[0008] In the first aspect of the present invention, a bamboo-based hard carbon material for sodium-ion batteries is provided. The preparation raw materials of the bamboo-based hard carbon material include: bamboo fiber, pore-forming agent, fluorine-containing polymer; wherein, the mass ratio of the bamboo fiber to the pore-forming agent is 0.8-1.2:1.

[0009] In order to further reduce costs and improve the electrochemical properties of the material, preferably, the pH value of the bamboo fiber in the present invention is 5-8, the residual gum rate is 15-25%, and the diameter is 100-300 μm.

[0010] Preferably, the bamboo fiber is one of Phyllostachys pubescens bamboo fiber, Neosinocalamus affinis bamboo fiber, and Sinocalamus atrovaginatus bamboo fiber.

[0011] More preferably, the bamboo fiber in the present invention is Phyllostachys pubescens bamboo fiber aged 2-5 years. It can be purchased from bamboo-producing areas such as Sichuan, Hunan, and Fujian. In the present invention, there is no specific limitation on the purchase origin of the bamboo fiber, and those skilled in the art can choose to purchase according to the actual situation.

[0012] When preparing the negative electrode material of a sodium-ion battery, the types of raw materials will directly affect the structure of the obtained hard carbon material, and the sodium storage performance of the hard carbon material as the negative electrode of a sodium-ion battery is determined by its structure. Especially, biomass-type materials have morphological inheritance, and their selection and treatment directly determine the structure of the hard carbon material. In the present invention, Phyllostachys pubescens bamboo fiber aged 2-5 years is used as a raw material. The bamboo fiber has rich pores and good consistency, and the obtained hard carbon material also has rich pores. Moreover, the used bamboo fiber raw material has a high purity and few impurities, which can reduce further impurity removal and other steps during preparation, greatly saving costs. The inventor also found that the hard carbon material obtained in the present invention has a higher closed pore content. When used as the negative electrode of a sodium-ion battery, it can greatly improve the sodium storage capacity of the negative electrode material. This may be because the lignin content in the bamboo fiber is relatively low, and it is easier to form closed pores after carbonization treatment.

[0013] Preferably, the pore-forming agent is one or a mixture of ammonium chloride, ammonium oxalate, ammonium hydrogen oxalate, ammonium carbonate, ammonium bicarbonate, and urea.

[0014] In order to make the prepared hard carbon material have a suitable specific surface area and further improve its cycling performance, preferably, the pore-forming agent is ammonium chloride.

[0015] In the structure of the hard carbon material, a larger specific surface area indicates that there are more defect sites in the material structure that can adsorb sodium ions, which is beneficial to the improvement of the "ramp region capacity"; however, at the same time, more electrolyte will decompose on the material surface to form a SEI film, resulting in a low initial Coulombic efficiency of the material. In the present invention, ammonium chloride is used as the pore-forming agent, which plays an activating pore-forming role in the pyrolysis treatment. Due to the moderate pore-forming ability of ammonium chloride, the prepared hard carbon material has a suitable specific surface area, good cycling performance and maintains a good initial Coulombic efficiency. Moreover, after ammonium chloride decomposes directly, there is no need to further wash the material to neutral, which greatly saves the preparation process and reduces the cost.

[0016] The inventors unexpectedly found that when using ammonium chloride as the pore-forming agent and bamboo fiber as the raw material, not much ammonium chloride is needed to greatly improve the specific surface capacity of the hard carbon material. The inventors analyzed that it may be because the HCl decomposed from ammonium chloride can further decompose the bamboo fiber, making the fiber structure looser and achieving the effect of deep pore formation. At the same time, the residual NH 4+ in the material can also act with the bamboo fiber to form a certain amount of nitrogen doping, thereby increasing the carbon layer spacing of the hard carbon material. The increase in the carbon layer spacing can not only provide a large number of reversible storage sites for sodium ions, but also promote the rapid diffusion of sodium ions between layers, thereby greatly improving the electrochemical performance of the material. However, it is necessary to pay attention to the usage amount of ammonium chloride and the settings of subsequent process conditions to achieve a performance balance between the sodium storage capacity and the initial Coulombic efficiency of the bamboo-based hard carbon material.

[0017] Preferably, the fluoropolymer is one or a mixture of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, and vinylidene chloride.

[0018] Preferably, the fluoropolymer is polytetrafluoroethylene.

[0019] More preferably, the number-average molecular weight of the polytetrafluoroethylene is 400000 - 800000. In the present invention, using polytetrafluoroethylene can further create pores and shape the bamboo fiber, promoting the formation of micropores; at the same time, the residual C can form a carbon layer on the surface of the bamboo fiber, improving the electrical conductivity of the hard carbon material.

[0020] The second aspect of the present invention provides a preparation method of a bamboo-based hard carbon material for a sodium ion battery. The specific steps of the preparation method are as follows:

[0021] Step S1: Pretreatment: Soak the original bamboo fiber in the pore-forming agent solution for 20 - 28 h, and then dry it at 80 °C for 10 - 14 h to obtain the pretreated original bamboo fiber;

[0022] Step S2: Pyrolysis treatment: Place the pretreated original bamboo fiber in an inert atmosphere furnace, pre-burn it at a pre-burning temperature of 400 - 800 °C for 6 - 10 h, and then cool it with the furnace to obtain the pre-burned original bamboo fiber; Mix the pre-burned original bamboo fiber with a fluoropolymer and ball-mill to obtain a mixture, then place the mixture in a high-temperature atmosphere furnace, calcine it at a calcination temperature of 1000 - 1300 °C for 4 - 8 h, cool it with the furnace and then ball-mill again, and sieve it to obtain the bamboo-based hard carbon material for sodium-ion batteries.

[0023] Preferably, in step S1, the concentration of the pore-forming agent solution is 10 - 30 g / L. For example, the concentrations of the pore-forming agent solution that can be listed are 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L, 21 g / L, 22 g / L, 23 g / L, 24 g / L, 25 g / L, 26 g / L, 27 g / L, 28 g / L, 29 g / L, 30 g / L, but it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0024] To make the pore-forming agent solution have a better soaking effect on the original bamboo fiber, preferably, in step S1, the solvent of the pore-forming agent solution is water and ethanol, and the mass ratio of water to ethanol is 1:1.

[0025] Preferably, in step S2, the mass of the fluoropolymer is 2 - 8% of the mass of the pre-burned original bamboo fiber.

[0026] Preferably, in step S2, the gas in the inert atmosphere furnace is nitrogen.

[0027] To obtain a nitrogen-doped hard carbon material and further improve the sodium storage capacity and first-cycle Coulombic efficiency of the hard carbon material, preferably, in step S2, the atmosphere in the high-temperature atmosphere furnace is NH3 and argon. More preferably, by mass percentage, the atmosphere in the high-temperature atmosphere furnace includes: 2 - 8% NH3 and 98 - 92% argon. Nitrogen doping can further increase the carbon layer spacing, provide a large number of reversible storage sites for sodium ions, and promote the rapid diffusion of sodium ions between layers. However, the content of NH3 cannot be too much, otherwise it will affect the electrochemical performance of the hard carbon material.

[0028] Preferably, the pre-burning temperature in step S2 is 500-700 °C. For example, the pre-burning temperature can be 500 °C, 520 °C, 540 °C, 560 °C, 580 °C, 600 °C, 620 °C, 640 °C, 660 °C, 680 °C, 700 °C, but is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0029] Preferably, in step S2, the heating rate during pre-burning is 0.5-3 °C / min. For example, the heating rate during pre-burning can be 0.5 °C / min, 0.6 °C / min, 0.7 °C / min, 0.8 °C / min, 0.9 °C / min, 1 °C / min, 1.1 °C / min, 1.2 °C / min, 1.3 °C / min, 1.4 °C / min, 1.5 °C / min, 1.6 °C / min, 1.7 °C / min, 1.8 °C / min, 1.9 °C / min, 2 °C / min, 2.1 °C / min, 2.2 °C / min, 2.3 °C / min, 2.4 °C / min, 2.5 °C / min, 2.6 °C / min, 2.7 °C / min, 2.8 °C / min, 2.9 °C / min, 3 °C / min, but is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0030] In the present invention, a pre-burning step is set, and the bamboo fiber is pre-carbonized at a relatively low temperature. By controlling the pre-burning temperature at 400-800 °C and the heating rate at 0.5-3 °C / min, the size of the mesopores in the hard carbon is controlled, achieving the effects of forming micropores / small mesopores and removing impurities. The formation of micropores / small mesopores is beneficial to the formation of closed pores after subsequent high-temperature calcination treatment. If the heating rate is set too high during the pre-burning process, the pore formation will be too large, affecting the closed pore content of the subsequent hard carbon material.

[0031] Preferably, the calcination temperature in step S2 is 1200 °C. A higher calcination temperature is more likely to promote the formation of closed pores and make the carbonization more complete. In the prior art, the sintering temperature is usually set to about 1500 °C; however, at the same time, a high calcination temperature is also more likely to form an ordered structure of microcrystalline graphite and reduce the carbon layer spacing, which is not conducive to the insertion and diffusion of sodium ions during the use of sodium-ion batteries. In the present invention, through the combined use of fluorine-containing polymers, the sintering temperature is effectively reduced, and sufficient carbonization can be achieved at a relatively low temperature, and more closed pores can be promoted to form.

[0032] Preferably, during the calcination, the heating rate is as follows: when the temperature is below 1000°C, the heating rate is 10 - 15°C / min; when the temperature is above 1000°C, the heating rate is 3 - 5°C / min. When the temperature is below 1000°C, the faster the heating rate, the more mesopores are formed after calcination, and more mesopores will transform into closed pores during subsequent heat preservation; at the same time, more defects are formed. A certain number of defect sites are beneficial to the insertion of sodium ions, but too many defect sites will deteriorate the material stability. If the heating rate is too slow, it is easy to promote the ordered arrangement of the carbon layer, improve the material conductivity but not suitable for storing sodium ions. Therefore, in the present invention, different heating rates are set under different temperature conditions, so that the prepared hard carbon material has appropriate defect sites and closed pore content, etc., and achieves a performance balance among the sodium storage capacity, Coulomb efficiency, and rate performance.

[0033] The third aspect of the present invention provides the application of the above-mentioned bamboo-based hard carbon material in the anode material of a sodium-ion battery.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) In the present invention, specific bamboo fibers are used, which not only reduce the production cost, but also the prepared hard carbon material has abundant pores and a high closed pore content.

[0036] (2) The present invention selects a specific pore-forming agent to be used in combination with bamboo fibers, so that the prepared hard carbon material has an appropriate specific surface area and carbon layer spacing, which can not only provide a large number of reversible storage sites for sodium ions, but also promote the rapid diffusion of sodium ions between layers, greatly improving the electrochemical performance of the material. And there is no need to further clean the material, which greatly saves the preparation process and reduces the cost.

[0037] (3) The fluoropolymer used in the present invention can form pores and shape the bamboo fibers, promote the generation of micropores, and improve the conductivity of the hard carbon material; at the same time, it can also reduce the calcination temperature in the pyrolysis treatment and optimize the pyrolysis conditions.

[0038] (4) During the pyrolysis treatment process of the present invention, temperature, heating rate, atmosphere, etc. will all have a great impact on the microscopic structures such as the graphitization degree, carbon layer spacing, porosity, and closed pore content of the obtained hard carbon material. In the present invention, by controlling the preparation process parameters such as pyrolysis temperature, pyrolysis heating rate, and atmosphere conditions, the prepared hard carbon material has an appropriate specific surface area, carbon layer spacing, pore structure, and closed pore content. Applying the bamboo-based hard carbon material of the present invention to a sodium-ion battery has excellent electrochemical performances such as reversible capacity, first-cycle Coulomb efficiency, and rate performance. Description of the Drawings

[0039] Figure 1 It is a product diagram of the bamboo fiber used in Example 1 of the present invention;

[0040] Figure 2 SEM image of the pre-baked bamboo fiber in Example 1 of the present invention;

[0041] Figure 3 SEM image of the bamboo-based hard carbon material prepared in Example 1 of the present invention;

[0042] Figure 4 XPS image of the bamboo-based hard carbon material prepared in Example 1 of the present invention;

[0043] Figure 5 XRD image of the bamboo-based hard carbon material prepared in Example 1 of the present invention;

[0044] Figure 6 Nitrogen adsorption / desorption isotherm of the bamboo-based hard carbon material prepared in Example 1 of the present invention;

[0045] Figure 7 Mesopore and macropore distribution map of the bamboo-based hard carbon material prepared in Example 1 of the present invention;

[0046] Figure 8 First charge-discharge curve of the bamboo-based hard carbon material prepared in Example 1 of the present invention;

[0047] Figure 9 Rate performance of the bamboo-based hard carbon material prepared in Example 1 of the present invention;

[0048] Figure 10 First charge-discharge curve of the bamboo-based hard carbon material prepared in Comparative Example 3 of the present invention. Detailed implementation manners

[0049] The technical solutions of the present invention will be described clearly and completely below. Apparently, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention. The present invention will be further explained below in conjunction with specific implementation manners.

[0050] Embodiment

[0051] Embodiment 1

[0052] This embodiment provides a preparation method of a bamboo-based hard carbon material for a sodium ion battery. The specific steps of the preparation method are as follows:

[0053] Step S1: Pretreatment: Place 20 g of moso bamboo primary fiber (2 - 5 years old, pH value of 6, residual gum rate of 20.4%, average diameter of 150 μm) in 1 L of ammonium chloride solution with a concentration of 20 g / L (the solvent is water and ethanol, and the mass ratio of water to ethanol is 1:1), soak for 24 h, and then dry at 80 °C for 12 h after sufficient soaking and absorption to obtain the pretreated primary fiber;

[0054] Step S2: Pyrolysis treatment: Place the pretreated primary fiber in a nitrogen atmosphere furnace, pre-burn at a pre-burning temperature of 600 °C for 8 h, and then cool with the furnace to obtain the pre-burned primary fiber. The heating rate during pre-burning is 2 °C / min; Mix the pre-burned primary fiber with polytetrafluoroethylene (the mass of polytetrafluoroethylene is 5% of the mass of the pre-burned primary fiber, and the number average molecular weight is 600000) by ball milling to obtain a mixture, and then place the mixture in a high-temperature atmosphere furnace (the atmosphere of the high-temperature atmosphere furnace is 5% NH3 + 95% Ar), calcine at a calcination temperature of 1200 °C for 6 h. When the calcination temperature is lower than 1000 °C, the heating rate is 12 °C / min; when it is higher than 1000 °C, the heating rate is 4 °C / min; After cooling with the furnace, ball mill again and pass through a 300-mesh sieve to obtain a bamboo-based hard carbon material for sodium-ion batteries.

[0055] The physical diagram of the raw materials in Example 1 is as Figure 1 shown. The moso bamboo primary fiber is uniform and has a smooth surface. The dust and epidermis on the bamboo surface have been removed, and the impurity content is low. Figure 2 This is the SEM of the material after pretreatment and pre-carbonization. It can be seen that the internal bamboo fibers and tissue structures are obvious, the structure is loose, and the degree of graphitization is too low to be directly used as the anode material for sodium-ion batteries. Figure 3 This is the SEM image of the final product. It can be seen that after ball milling and mixing with polytetrafluoroethylene and high-temperature carbonization, the material has shrunk by more than 50%, there is no large tissue structure, and a variety of through holes and macropores appear on the surface. To analyze the nitrogen doping effect of ammonia, X-ray photoelectron spectroscopy (XPS) was used to analyze the product material of Example 1, and the data is as Figure 4 shown. It can be seen from the XPS total spectrum that the peak of C1s is extremely strong, and the main phase of the material is composed of carbon elements. The characteristic peak of N1s can also be seen, which proves that through the combined action of ammonia and the previous pore-forming agent, nitrogen elements have been successfully doped into the carbon lattice. The XRD of the product is as Figure 5As shown, it can be seen that it is a typical hard carbon feature. Referring to the provisions in Appendix E of GB / T 24533-2019, through the calculation of the (002) crystal plane, the carbon layer spacing d(002) = 0.388 nm can be obtained. The specific surface area, pore size and true density of the material are measured by the BET method for the specific surface area of solid substances in accordance with GB / T 19587 Gas Adsorption, and directly tested using the BET single-point method data for the specific surface area, the T-plot model data for micropores (less than 2 nm) to calculate the total micropore volume, and the BJH model data for mesopores (2 - 50 nm) and macropores (>50 nm). The nitrogen adsorption / desorption isotherm is as Figure 6 shown, which are typical type I and type IV characteristics, proving that there are both micropores and a large number of mesopores in the material. The micropore structure has the function of storing charge, and the mesopore structure enables the electrolyte to fully penetrate the material, promoting the rapid diffusion of Na + . The micropore volume of the product of Example 1 is 0.01835 cm 3 / g. As Figure 7 shown is the mesopore and macropore distribution of the product material of Example 1. It can be seen that there are hierarchical pore distribution characteristics, and the mesopores are concentrated at 2.1, 2.9, 3.2, 5.1, 38, 62 nm; the specific surface area of the product is 27.7 m 2 / g, and the true density is 1.85 g / cm 3 . The true density is directly related to the closed pore content in the material. Theoretically, the density of carbon materials is 2.2 - 2.3 g / cm 3 . It can be seen that the product of Example 1 has abundant closed pores, and the closed pores are beneficial to the adsorption of sodium ions. According to the hard carbon standard of GB / T43114-2023, the product material is assembled with a sodium metal sheet into a coin-type half-cell to test the relevant electrochemical properties, including the first charge specific capacity, the first Coulombic efficiency, and the rate performance. As Figure 8 shown is the first charge-discharge curve of the product material of Example 1, Figure 9 and

[0056] Example 2

[0057] This example also provides a preparation method of a bamboo-based hard carbon material for sodium ion batteries. The specific steps of the preparation method are as follows:

[0058] Step S1: Pretreatment: Place 20 g of moso bamboo primary fibers (2 - 5 years old, pH value of 8, residual gum rate of 24.1%, average diameter of 240 μm) in 1 L of ammonium oxalate solution with a concentration of 18 g / L (the solvent is water and ethanol, and the mass ratio of water to ethanol is 1:1), soak for 24 h, and after sufficient soaking and absorption, dry at 80 °C for 12 h to obtain pretreated primary bamboo fibers;

[0059] Step S2: Pyrolysis treatment: Place the pretreated primary bamboo fibers in a nitrogen atmosphere furnace, pre-burn at a pre-burning temperature of 650 °C for 7 h, and then cool with the furnace to obtain pre-burned primary bamboo fibers. The heating rate during pre-burning is 1.5 °C / min; Mix the pre-burned primary bamboo fibers with polyvinylidene fluoride (the mass of polyvinylidene fluoride is 4% of the mass of the pre-burned primary bamboo fibers, and the number-average molecular weight is 200,000) and ball-mill to obtain a mixture. Then place the mixture in a high-temperature atmosphere furnace (the atmosphere of the high-temperature atmosphere furnace is 3% NH3 + 97% Ar), calcine at a calcination temperature of 1250 °C for 5 h. When the calcination temperature is lower than 1000 °C, the heating rate is 14 °C / min; when it is higher than 1000 °C, the heating rate is 3 °C / min; After cooling with the furnace, ball-mill again and pass through a 300-mesh sieve to obtain a bamboo-based hard carbon material for sodium-ion batteries.

[0060] According to the same test method as in Example 1, it can be measured that d(002) of the product material in Example 2 is 0.384 nm, the micropore volume is 0.01714 cm 3 / g, the specific surface area is 29.2 m 2 / g, and the true density is 1.99 g / cm 3 . The initial charge specific capacity of the material is 334.1 mAh / g, and the initial Coulomb efficiency is 90.11%.

[0061] Example 3

[0062] This example also provides a preparation method of a bamboo-based hard carbon material for sodium-ion batteries. The specific steps of the preparation method are as follows:

[0063] Step S1: Pretreatment: Place 20 g of moso bamboo primary fibers (2 - 5 years old, pH value of 7, residual gum rate of 15.6%, average diameter of 100 μm) in 1 L of ammonium carbonate solution with a concentration of 24 g / L (the solvent is water and ethanol, and the mass ratio of water to ethanol is 1:1), soak for 24 h, and after sufficient soaking and absorption, dry at 80 °C for 12 h to obtain pretreated primary bamboo fibers;

[0064] Step S2: Pyrolysis treatment: Place the pretreated bamboo fiber in a nitrogen atmosphere furnace. After pre-burning at a pre-burning temperature of 500 °C for 10 h, cool it with the furnace to obtain the pre-burned bamboo fiber. The heating rate during pre-burning is 0.5 °C / min. Mix the pre-burned bamboo fiber with chlorotrifluoroethylene (the mass of chlorotrifluoroethylene is 8% of the mass of the pre-burned bamboo fiber) and ball-mill to obtain a mixture. Then place the mixture in a high-temperature atmosphere furnace (the atmosphere of the high-temperature atmosphere furnace is 8% NH3 + 92% Ar), and calcine at a calcination temperature of 1000 °C for 8 h. When the calcination temperature is lower than 1000 °C, the heating rate is 10 °C / min; when it is higher than 1000 °C, the heating rate is 3 °C / min. After cooling with the furnace, ball-mill again and pass through a 300-mesh sieve to obtain the bamboo-based hard carbon material for sodium-ion batteries.

[0065] According to the same test method as in Example 1, it can be measured that d(002) of the product material in Example 3 is 0.399 nm, the micropore volume is 0.02445 cm 3 / g, and the specific surface area is 33.2 m 2 / g, and the true density is 1.94 g / cm 3 . The initial charge specific capacity of the material is 331.8 mAh / g, and the initial Coulomb efficiency is 90.20%.

[0066] Example 4

[0067] This example also provides a preparation method of a bamboo-based hard carbon material for sodium-ion batteries. The specific steps of the preparation method are as follows:

[0068] Step S1: Pretreatment: Place 20 g of bamboo fiber from Phyllostachys pubescens (2 - 5 years old, pH value of 5, residual gum rate of 24.8%, average diameter of 300 μm) in 1 L of a urea solution with a concentration of 16 g / L (the solvent is water and ethanol, and the mass ratio of water to ethanol is 1:1), soak for 24 h. After sufficient soaking and absorption, dry it at 80 °C for 12 h to obtain the pretreated bamboo fiber;

[0069] Step S2: Pyrolysis treatment: Place the pretreated bamboo fiber in a nitrogen atmosphere furnace. After pre-burning at a pre-burning temperature of 700 °C for 6 h, cool it with the furnace to obtain the pre-burned bamboo fiber. The heating rate during pre-burning is 3 °C / min. Mix the pre-burned bamboo fiber with tetrafluoroethylene-hexafluoropropylene copolymer (the mass of the tetrafluoroethylene-hexafluoropropylene copolymer is 2% of the mass of the pre-burned bamboo fiber) and ball-mill to obtain a mixture. Then place the mixture in a high-temperature atmosphere furnace (the atmosphere of the high-temperature atmosphere furnace is 3% NH3 + 97% Ar), and calcine it at a calcination temperature of 1300 °C for 4 h. When the calcination temperature is lower than 1000 °C, the heating rate is 15 °C / min; when it is higher than 1000 °C, the heating rate is 5 °C / min. After cooling with the furnace, ball-mill again and pass through a 300-mesh sieve to obtain the bamboo-based hard carbon material for sodium-ion batteries.

[0070] According to the same testing method as in Example 1, it can be measured that the d(002) of the product material in Example 4 is 0.376 nm, and the micropore volume is 0.01576 cm 3 / g, and the specific surface area is 21.5 m 2 / g, and the true density is 1.81 g / cm 3 . The initial charge specific capacity of the material is 338.6 mAh / g, and the initial Coulombic efficiency is 89.97%.

[0071] Comparative Example 1

[0072] This comparative example also provides a preparation method of a bamboo-based hard carbon material for sodium-ion batteries. The specific implementation manner is the same as that in Example 1. The difference from Example 1 is that in step S2 of this comparative example: Pyrolysis treatment: Mix the pretreated bamboo fiber with polytetrafluoroethylene (the mass of polytetrafluoroethylene is 5% of the mass of the pretreated bamboo fiber) and ball-mill to obtain a mixture. Then place the mixture in a high-temperature atmosphere furnace (the atmosphere of the high-temperature atmosphere furnace is 5% NH3 + 95% Ar), and calcine it at a calcination temperature of 1200 °C for 6 h. When the calcination temperature is lower than 1000 °C, the heating rate is 12 °C / min; when it is higher than 1000 °C, the heating rate is 4 °C / min. After cooling with the furnace, ball-mill again and pass through a 300-mesh sieve to obtain the bamboo-based hard carbon material for sodium-ion batteries. According to the same testing method as in Example 1, it can be measured that the micropore volume of the product material in Comparative Example 1 is 0.00794 cm 3 / g, and the true density is 2.13 g / cm 3 . The initial charge specific capacity of the material is 284.0 mAh / g, and the initial Coulombic efficiency is 83.17%. That is, without pre-burning and the lack of sufficient micropores and closed pores, the overall performance of the material decreases.

[0073] Comparative Example 2

[0074] This comparative example also provides a preparation method of bamboo-based hard carbon materials for sodium-ion batteries. The specific implementation method is the same as that of Example 1. The difference from Example 1 is that in step S1 of this comparative example, the concentration of the ammonium chloride solution is 10 g / L ammonium chloride solution.

[0075] According to the same test method as in Example 1, the micropore volume of the product material of Comparative Example 2 can be measured to be 0.01644 cm 3 / g, and the specific surface area is 15.2 m 2 / g. The rate performance retention rate of the material at 2C / 0.2C is 23.72%. Due to the lack of pore-forming agent, the macropores and mesopores are missing, which further affects the specific surface area and micropores. The difficulty of sodium ion insertion increases, the resistance increases, and the rate performance deteriorates.

[0076] Comparative Example 3

[0077] This comparative example also provides a preparation method of bamboo-based hard carbon materials for sodium-ion batteries. The specific implementation method is the same as that of Example 1. The difference from Example 1 is that in step S2 of this comparative example, no polytetrafluoroethylene is added.

[0078] According to the same test method as in Example 1, the micropore volume of the product material of Comparative Example 3 can be measured to be 0.01253 cm 3 / g. As Figure 10 shown, the initial charge specific capacity of the product material of Comparative Example 3 is 315.2 mAh / g, the initial Coulomb efficiency is 88.74%, and the rate performance retention rate at 2C / 0.2C is 28.45%. Without the promotion of fluorides such as polytetrafluoroethylene, the number of micropores decreases, and at the same time the conductivity decreases. Both the initial Coulomb efficiency and capacity decrease, and the rate performance deteriorates.

[0079] Comparative Example 4

[0080] This comparative example also provides a preparation method of bamboo-based hard carbon materials for sodium-ion batteries. The specific implementation method is the same as that of Example 1. The difference from Example 1 is that in step S2 of this comparative example, the atmosphere in the high-temperature atmosphere furnace is 100% Ar.

[0081] According to the same test method as in Example 1, the d(002) of the product material of Comparative Example 4 can be measured to be 0.372 nm. The initial charge specific capacity of the material is 304.9 mAh / g, the initial Coulomb efficiency is 82.43%, and the rate performance retention rate at 2C / 0.2C is 9.88%. The doping effect of ammonia on the hard carbon material is extremely obvious. Nitrogen-doped carbon can greatly increase its layer spacing and promote the entry of sodium ions. The rate performance of the undoped material is extremely poor.

[0082] Comparative Example 5

[0083] This comparative example also provides a preparation method of a bamboo-based hard carbon material for a sodium-ion battery. The specific implementation manner is the same as that of Example 1. The difference from Example 1 is that in step S2 of this comparative example, the calcination temperature of the atmosphere in the high-temperature atmosphere furnace is 1500 °C.

[0084] According to the same test method as in Example 1, it can be measured that d(002) of the product material of Comparative Example 5 is 0.373 nm, and the micropore volume is 0.00822 cm 3 / g, and the specific surface area is 18.5 m 2 / g, and the true density is 2.04 g / cm 3 . The initial charge specific capacity of the material is 277.8 mAh / g, the initial Coulomb efficiency is 78.69%, and the rate performance retention rate of 2C / 0.2C is 0.33%. The increase in temperature significantly improves the graphitization degree of the hard carbon material, and its layer spacing decreases, but it also significantly reduces the micropores, specific surface area, and closed pore content of the hard carbon material, resulting in difficulty for sodium ions to enter the material, and thus the performance is extremely poor.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A bamboo-based hard carbon material for sodium ion batteries, characterized in that: The raw materials for preparing the bamboo-based hard carbon material include: bamboo fiber, pore-forming agent, and fluorine-containing polymer; wherein the mass ratio of the bamboo fiber to the pore-forming agent is 0.8-1.2:

1.

2. The bamboo-based hard carbon material for sodium ion battery according to claim 1, characterized in that: The pH value of the bamboo fiber is 5-8, the residual glue rate is 15-25%, and the diameter is 100-300 μm.

3. The bamboo-based hard carbon material for sodium ion battery according to claim 1, characterized in that: The pore-forming agent is one of ammonium chloride, ammonium oxalate, ammonium hydrogen oxalate, ammonium carbonate, ammonium hydrogen carbonate and urea, or a mixture of the two or more.

4. The bamboo-based hard carbon material for sodium ion battery according to claim 1, characterized in that: The fluorine-containing polymer is one or a mixture of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, and trifluorochloroethylene.

5. The method for preparing a bamboo-based hard carbon material for sodium ion battery according to any one of claims 1 to 4, characterized in that: The specific steps of the preparation method are as follows: Step S1: pretreatment: soaking the bamboo fibers in a pore-forming agent solution for 20-28 hours, drying them at 80° C. for 10-14 hours, and obtaining pretreated bamboo fibers; Step S2: Pyrolysis treatment: placing the pretreated bamboo fiber in an inert atmosphere furnace, pre-burning it at a pre-burning temperature of 400-800° C. for 6-10 hours, and cooling it with the furnace to obtain pre-burned bamboo fiber; The pre-burned bamboo fiber and the fluorine-containing polymer are mixed and ball-milled to obtain a mixture, and then the mixture is placed in a high-temperature atmosphere furnace and calcined at a calcination temperature of 1000-1300°C for 4-8 hours. After cooling with the furnace, the mixture is ball-milled again and sieved to obtain a bamboo-based hard carbon material for sodium ion batteries.

6. The method for preparing a bamboo-based hard carbon material for sodium ion battery according to claim 5, characterized in that: In step S1, the concentration of the pore-forming agent solution is 10-30 g / L.

7. The method for preparing a bamboo-based hard carbon material for sodium ion battery according to claim 5, characterized in that: The mass of the fluorine-containing polymer in step S2 is 2-8% of the mass of the pre-burned bamboo fiber.

8. The method for preparing a bamboo-based hard carbon material for sodium ion battery according to claim 5, characterized in that: In step S2, the atmosphere in the high temperature atmosphere furnace is NH3 and argon.

9. The method for preparing a bamboo-based hard carbon material for sodium ion battery according to claim 5, characterized in that: In step S2, the heating rate during the pre-firing is 0.5-3°C / min.

10. Application of bamboo-based hard carbon material in negative electrode material of sodium ion battery, characterized in that: The bamboo-based hard carbon material is a bamboo-based hard carbon material for sodium ion batteries according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Bamboo charcoal preparation method capable of realizing large-scale production and application of bamboo charcoal in sodium-ion battery

    CN114890404A

  • Bamboo-based hard carbon material, preparation thereof and application of bamboo-based hard carbon material in sodium ion battery

    CN117105199A

Cited By

  • Composite hard carbon negative electrode material, preparation method thereof and battery

    CN122010090A

  • Preparation method of biomass hard carbon negative electrode material based on deep eutectic solvent treatment and application of biomass hard carbon negative electrode material in sodium-ion battery negative electrode

    CN122079129A